Trust, trustworthiness and the consensus effect: An evolutionary approach - Fabrizio Adriani; Silvia Sonderegger (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2013)
People often form expectations about others using the lens of their own attitudes (the so-called consensus effect). We study the implications of this for trust and trustworthiness. Trustworthy individuals are more " than opportunists and are accordingly less afraid to engage in market-based exchanges, where they may be vulnerable to opportunistic behavior. In some cases, the material benefits from greater market participation may compensate for the costs of being trustworthy. We use an indirect evolutionary approach to endogenize preferences for trustworthiness, showing that a polymorphic equilibrium (where both trustworthiness and opportunism coexist in the population) may be evolutionarily stable. Better institutions limiting the scope for opportunism may favor the spreading of trustworthiness (crowding in), but the opposite (crowding out) may also occur. Our analysis is consistent with experimental evidence.
Keywords: C73; D02; D03; D82; Z1; 330; Endogenous Preferences; Trust; Consensus Effect; Institutions; Crowding Out